Paratesticular Serous Borderline Tumor in a Pediatric Patient - Itzel Araceli Ortiz Meza; Marco Antonio Ponce Camacho; Rodolfo Franco Márquez; Mauricio Delgado Morquecho; Raquel Garza Guajardo; Oralia Barboza Quintana (Hindawi Limited, 2020)
Tumors of the paratesticular region are generally tumors of slow growth, with little symptomatology and, in most cases, benign in nature; in this area, a borderline serous tumor may arise hypothetically from Müllerian metaplasia of the tunica vaginalis, which is histologically identical to its ovarian counterpart. We present a 10-year-old male, with right gynecomastia and ipsilateral hydrocele, showing an enlarged right testicle with a volume of 12 ml and a left testicle with a volume of 10 ml. A right orchiectomy was performed, which presented a poorly defined tan tumor of 1.8 cm that occupied the vaginal and epididymal tunica, and infiltrates the testicular parenchyma. Histological sections revealed a cystic neoplasm, with hierarchical papillary projections, covered by one or several epithelial columnar and hobnail cells with moderate atypia and scant mitosis. Immunohistochemical reactions were performed, resulting positive for PAX-8, epithelial membrane antigen, and CK7, confirming the diagnosis of borderline serous tumor. Since the first reported case in 1986, few have been reported, the majority of these in adults with only three cases in children. In the few cases reported, the prognosis is usually favorable after surgical resection, with disease-free follow-up for up to 18 years.